2022
DOI: 10.3390/jcm11195654
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein as Predictor for Infectious Complications after Robotic and Open Esophagectomies

Abstract: Introduction: The value of C-reactive protein (CRP) as a predictor of anastomotic leakage (AL) after esophagectomy has been addressed by numerous studies. Despite its increasing application, robotic esophagectomy (RAMIE) has not been considered separately yet in this context. We, therefore, aimed to evaluate the predictive value of CRP in RAMIE. Material and Methods: Patients undergoing RAMIE or completely open esophagectomy (OE) at our University Center were included. Clinical data, CRP- and Procalcitonin (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“… 53 The incidence of postoperative pneumonia ranged from 0% to 45.4%; however, the literature varied in its definition and criteria influencing treatment decisions. 42 Notably, Meredith et al reported no significant difference in the incidence of pneumonia between patients undergoing open, robotic or conventional minimally invasive esophagectomy. 52 In comparison, three studies reported an incidence of postoperative pneumonia of >30%, despite all patients undergoing laparoscopic and robotic phases, suggesting a multifactorial aetiology for postoperative pneumonia.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“… 53 The incidence of postoperative pneumonia ranged from 0% to 45.4%; however, the literature varied in its definition and criteria influencing treatment decisions. 42 Notably, Meredith et al reported no significant difference in the incidence of pneumonia between patients undergoing open, robotic or conventional minimally invasive esophagectomy. 52 In comparison, three studies reported an incidence of postoperative pneumonia of >30%, despite all patients undergoing laparoscopic and robotic phases, suggesting a multifactorial aetiology for postoperative pneumonia.…”
Section: Discussionmentioning
confidence: 98%
“…With sufficient experience, centres may then be able to match higher-volume American and Chinese units. 42 49 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoalbuminemia in patients with aSAH not only reduces the level of immune protein and obstructs the repair of the mucosal barrier, leading to increased susceptibility to infection, but also exacerbates brain edema after subarachnoid hemorrhage, ultimately worsening motor function impairment in patients ( 32 , 35 ). Some recent experimental findings additionally indicate that albuminemia mediates its neuroprotection through neurovascular remodeling and reducing cerebral lesions ( 36 38 ). A pilot study revealed that 1.25 g/kg/day albumin treatment was safe in SAH patients and might produce a better outcome ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…CRP is a well-known biomarker of systemic inflammation ( 29 ). An increasing body of evidence suggests that CRP can predict various postoperative infections ( 30 – 32 ). Our study also indicated that monitoring serum CRP levels can be useful in predicting POP in patients with aSAH.…”
Section: Discussionmentioning
confidence: 99%